Comparison of Nasal CPAP versus Bi-level CPAP in Transient Tachypnea of the Newborn: A Randomized Trial - Özer Bekmez, Buse; Dizdar, Evrim Alyamaç; Büyüktiryaki, Mehmet; Sari, Fatmanur; Uraş, Nurdan; Canpolat, Fuat Emre; Oğuz, Şerife Suna (American Journal of Perinatology, 2020)
Objective The optimal noninvasive ventilation (NIV) modality in the treatment of transient tachypnea of the newborn (TTN) is still unknown. The aim of this study was to compare nasal continuous positive airway pressure (NCPAP) versus bi-level CPAP in the treatment of TTN.Study Design This was a prospective randomized study that was conducted in a tertiary level neonatal intensive care unit of Zekai Tahir Burak Women's Health Education and Research Hospital during the 1-year period between April 2017 and March 2018. The study included infants at ≥34 gestational weeks and birth weight ≥2,000 g who were diagnosed with TTN. The patients were randomized to either NCPAP or bi-level CPAP groups as initial respiratory support. The primary outcome was the rate of NIV failure.Results A total of 151 infants were incorporated into the study. The intubation rate was significantly higher in the NCPAP group (15/75) compared with the bi-level CPAP group (6/76) (p = 0.032). There was a significant decrease in the level of pCO2 at the 12 (60.7 ± 6.7 vs. 66.3 ± 8.8, p = 0.017) and 24 (50 ± 8 vs. 53 ± 10, p = 0.028) hours of NIV in the bi-level CPAP group compared with the NCPAP group. Duration of NIV, total respiratory support, hospital stay, and the incidence of pneumothorax were similar between the groups.Conclusion Bi-level CPAP reduced the rate of NIV failure and pCO2 levels at the 12 and 24 hours in late preterm and term infants with a diagnosis of TTN.Key Points
Keywords: noninvasive ventilation; transient tachypnea of the newborn; NCPAP; bi-level CPAP